1989
DOI: 10.1021/bi00445a024
|View full text |Cite
|
Sign up to set email alerts
|

Castanospermine inhibits the function of the low-density lipoprotein receptor

Abstract: Castanospermine, a plant alkaloid that inhibits the glycoprotein processing enzyme glucosidase I, has been used to inhibit N-linked oligosaccharide modification, resulting in the production of glycoproteins having Glc3Man7-9(GlcNAc)2 oligosaccharides. This alkaloid caused a significant inhibition of LDL endocytosis in cultured primate smooth muscle cells and human skin fibroblasts. At an optimum concentration of 250 micrograms/mL, castanospermine caused a 40% decrease in cell surface receptor-mediated LDL bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Cell fractionation studies indicated that DNJ caused an accumulation of a1 -antitrypsin in the ER, suggesting that the presence of glucose on the N-linked oligosaccharide might retard the transfer of the glycoprotein from the ER to the Golgi apparatus [66]. Similar results were obtained with regard to the synthesis and targeting of the low density lipoprotein receptor in smooth muscle cells grown in the presence of castanospermine [67]. and in the synthesis and targeting of the insulin receptor in the presence of DNJ or castanospermine [68].…”
Section: Glucosidase Inhibitorssupporting
confidence: 74%
“…Cell fractionation studies indicated that DNJ caused an accumulation of a1 -antitrypsin in the ER, suggesting that the presence of glucose on the N-linked oligosaccharide might retard the transfer of the glycoprotein from the ER to the Golgi apparatus [66]. Similar results were obtained with regard to the synthesis and targeting of the low density lipoprotein receptor in smooth muscle cells grown in the presence of castanospermine [67]. and in the synthesis and targeting of the insulin receptor in the presence of DNJ or castanospermine [68].…”
Section: Glucosidase Inhibitorssupporting
confidence: 74%
“…They share sequence motifs, bind calcium, and serve as molecular chaperones. Whereas their precise role in the maturation of glycoproteins has yet to be fully elucidated, the effects of glucosidase inhibitors on protein maturation indicate that they are important for the efficient and timely folding, retention, and possibly oligomeric assembly of glycoproteins (Edwards et al, 1989;Pal et al, 1989;Bergeron et al, 1994;Hammond and Helenius, 1994a). It will be interesting to determine whether other proteins sharing sequence homology with these chaperones (CNE1 of Saccharomyces cerevisiae, RALl of Onchocerca volvulus, and p407 of Aplysia californica or the surface protein of adherent melanoma cells (White et al, 1994)), might share similar lectin properties.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, a 24-h incubation period resulted in a 50% reduction of surface receptors. Similarly, a CST-induced decrease (40%) in expression of the integral membrane low-density lipoprotein receptor has been reported and ascribed to a mechanism involving receptor redistribution (52).…”
Section: Discussionmentioning
confidence: 99%